2009
DOI: 10.1007/s11655-009-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginkgo leaf extract on vascular endothelial function in patients with early stage diabetic nephropathy

Abstract: GLE could decrease the plasma level of vWF, raise the plasma NO level and improve the endothelium dependent vascular dilating function in DN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…Astragalus and its active extracts have been integrated in clinical management of diabetes mellitus (Huang and Lu, 2003) and early DN with satisfying safety profiles (Liu et al, 2001), partly for its protective effect against oxidative stress as a free radical scavenger (Toda and Shirataki, 1999). Although widely used for thousands of years, our knowledge is still limited about the mechanism of Astragalus in renal diseases especially in diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus and its active extracts have been integrated in clinical management of diabetes mellitus (Huang and Lu, 2003) and early DN with satisfying safety profiles (Liu et al, 2001), partly for its protective effect against oxidative stress as a free radical scavenger (Toda and Shirataki, 1999). Although widely used for thousands of years, our knowledge is still limited about the mechanism of Astragalus in renal diseases especially in diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…12 Some agents that can interfere with TGF-b1 expression in kidney cells have shown to be effective in treating diabetic kidney fibrosis. 13 In our previous study, we found astragalus membranous inhibits TGF-b1 protein and mRNA over expression in renal cortex of diabetic rats suggesting that ASI might play a beneficial role in experimental DN, at least, partly by inhibiting TGF-b1 expression in kidney. 7 We also found astragalus membranous can exert a renal protection on DN, possibly partly through the reduction of TGF-b1 and big-h3 expression.…”
Section: Discussionmentioning
confidence: 82%
“…Chronic treatment with OLE inhibited the high glucose-induced neural damage and suppressed diabetesinduced thermal hyperalgesia observed in diabetic rat (24). Additionally, the chronic treatment with GLE improved the vascular function in diabetic nephrotic patients (25). Recently, OLE has been reported for its potential hypoglycemic activity following chronic systemic administration in overweight middle-aged men who are at risk of developing the metabolic syndrome as well as in experimental animals (10,26).…”
Section: Discussionmentioning
confidence: 99%